Manajemen Pariwisata Hutan Wisata Tinjomoyo Kota Semarang - Rian Guntoro Adi; Hesti Lestari; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The background of this research is the problems of tourism management of the Tinjomoyo Tourism Forest. The purpose of this study is to analyze tourism management in the Tinjomoyo Tourism Forest and its driving and inhibiting factors. The theory used is the theory of public management functions by Garson and Overman and the theory of tourism management functions by Damanik and Teguh. This study uses a qualitative descriptive method with snowball sampling technique. The results showed that tourism management in the Tinjomoyo Tourism Forest had not been running well. There are management functions that have not been implemented well, namely planning functions, finance functions, organizing functions, and implementation functions. The functions that have been implemented quite well are the relationship function, information function, and control function. Factors that drive the success of the management function are collaboration with other agencies, disciplined employees in collecting data, and firm leadership. There are also inhibiting factors, namely the lack of involvement of UPTD Tinjomoyo and the community in planning, refocusing the budget due to COVID-19, lack of investor interest, poor communication, lack of human resources, budget constraints, and unstable land conditions. Suggestions that can be given by researchers are that the management of the Tinjomoyo Tourism Forest must empower the surrounding community, find investors for resources, improve communication between UPTD Tinjomoyo and the Semarang City Culture and Tourism Office, and avoid development on slopes.